Antologi Puisi Peluklah Aku Karya Frans Nadjira: Kajian Ekologi Sastra - Monita Br Sinaga; I Gusti Ayu Agung Mas Triadyani; I Ketut Sudewa (Stilistika : Journal of Indonesian Language and Literature, 2022)
This research uses the object of the poetry anthology Peluklah Aku which is studied from the point of view of literary ecology. The anthology of the poem Peluklah Aku is chosen as the object of research because in this book many symbols of nature are related to the study that the researcher is doing. The analysis in this study includes an analysis of the physical structure of poetry, an analysis of the inner structure of poetry, and the representation of nature contained in the anthology of the poem Peluklah Aku. The theory used is the literary ecology theory of Suwardi Endraswara and the structural theory of Herman Waluyo's poetry. The method used in collecting data is a literature study method with reading, listening, and note-taking techniques. The process of data analysis used the descriptive-analytical method with reading, listening, note-taking, and interpretation techniques. Presentation of data analysis using analytical descriptive techniques using a variety of scientific language, data analysis presentation techniques using a predetermined thesis writing format. Based on the analysis, the following findings were obtained. First, the poems that have been analyzed consist of different themes including the themes of social criticism, social protest, struggle, love, hope, messages, advice, death, and nostalgia. Second, the natural symbols used by the poet in his poems are not to give messages to protect the environment or related to the environment. Natural signs used by the poet in his poems are natural features that have similar characteristics to the situation or the message the poet wants to convey to the reader. This is done by the poet to disguise the true purpose and purpose of a poem being created.